Modeling and assessing Highly Pathogenic Avian Influenza (HPAI) spread, epidemiological control measures, and cost - Eihab Fathelrahman; Magdi Mohamed Ali; Tamrat Gebiso Challa; Raeda Osman; Adil I. Elawad; Mervat H. AL Nuaimat; Meera M. Saeed; Yassir M. Eltahir; Oum-Keltoum Bensalah; Youssef El-Khatib; Aaron Reeves (PLoS ONE, 2026)
Highly Pathogenic Avian Influenza (HPAI) is a highly contagious, transboundary disease that can affect animals and humans, posing significant health risks to both. This study aimed to prepare for a potential outbreak by modelling the spread of HPAI using stochastic methods with the customized North American Animal Disease Spread Model (NAADSM) software © , which was tailored specifically for the UAE. Information from 46 commercial poultry farms, including parents, broilers, and layers, was used. This investigation simulated one baseline scenario without intervention and three disease control methods. The scenarios are baseline (without any disease-spread intervention; scenario 1), movement control strategy (scenario 2), intensive vaccination strategy (scenario 3), and depopulation of poultry farms (scenario 4). The model generated outputs on the number of farms and the number of birds infected, vaccinated, or depopulated, as well as the duration of the disease outbreak. The results indicated that the depopulation strategy, scenario 4, led to the lowest epidemic impact and the shortest outbreak duration (16 days), compared with scenarios 1, 2, and 3, which had outbreak durations of 26, 32, and 31 days, respectively. The results of this study help decision-makers determine the optimal control strategy to combat HPAI. Such a strategy minimizes the consequences of the disease spread and the associated implementation costs.